2023
DOI: 10.1186/s13018-023-03787-5
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and factors influencing neck shortening after screw fixation of femoral neck fractures with the femoral neck system

Abstract: Objective To investigate the effects of postoperative femoral neck shortening in patients with femoral neck fractures fixed with femoral neck system screws (FNS) and to explore the factors influencing femoral neck shortening. Method To retrospectively analyze the data of 113 patients with femoral neck fractures admitted to the Second Hospital of Fuzhou City, affiliated with Xiamen University, between December 2019 and January 2022. Of these, 87 pat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…Although the FNS has greater resistance to rotation and collapse, and at the same time, during weight bearing, repeated compression of the fracture, and resorption of the fracture during the healing process, the patients were more prone to shortening of the femoral neck in the early postoperative period. As reported in this study and other literature, the occurrence of shortening was mainly concentrated within 3 months postoperatively [ 8 ]..…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Although the FNS has greater resistance to rotation and collapse, and at the same time, during weight bearing, repeated compression of the fracture, and resorption of the fracture during the healing process, the patients were more prone to shortening of the femoral neck in the early postoperative period. As reported in this study and other literature, the occurrence of shortening was mainly concentrated within 3 months postoperatively [ 8 ]..…”
Section: Discussionsupporting
confidence: 74%
“…FNS has been used in clinical practice for a relatively short period of time, and there are many reports of complications such as fracture nonunion and femoral head necrosis, but there are fewer reports of postoperative femoral neck shortening. Femoral neck shortening is a relatively common complication in the early stage of the process, with an incidence rate of 8.3–10.0% reported in the literature [ 16 , 17 ], and there are also reports that the incidence rate of femoral neck shortening after fixation ranges from 28% to 39.1% [ 8 , 18 ], and there is a wide variation in the incidence rates reported in different studies. To clarify the differences in the incidence of femoral neck shortening after FNS fixation for different fracture types, this study was analyzed according to different fracture types and found that there were no cases of moderate or severe shortening in no-displaced femoral neck fractures, and the incidence of moderate and severe shortening in displaced FNF was 29.2% and 58.2%, and a total of 87.5% (21/24) of displaced FNF had shortening greater than 5 mm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation